Genotoxic stress triggers the activation of IRE1α-dependent RNA decay to modulate the DNA damage response - Estefanie Dufey (Nature Portfolio, 2020)
IRE1α plays a key role in the unfolded protein response (UPR) by promoting the unconventional splicing of the XBP1 and the selective cleavage of RNAs. Here the authors report that IRE1α is activated upon the DNA damage response and selectively controls the stability of mRNAs to maintain genome integrity.